Witholding Taxes and the Cost of Public Debt - Huizinga, Harry (IMF Working Papers; Working Paper ;, 1994)
Several industrialized countries impose withholding taxes on public interest accruing to nonresidents. This paper examines the international incidence of such withholding taxes by estimating to what extent these taxes raise the cost of government borrowing. It is found that the pretax interest rate is most sensitive to the tax withheld on Japanese investors. In particular, the gross-up is about half of this tax, which suggests that about half is returned to the investor in the form of foreign tax credits. The extent of the gross-up rises over the 1989-93 period, which indicates that in recent years foreign tax credits have been available to a lesser extent.